Діагностика підшипників ковзання прокатного обладнання - Гайдамака, Анатолій Володимирович; Музикін, Юрій Дмитрович; Бородін, Дмитро Юрійович; Верба, Ілля Сергійович; Кригін, Сергій Володимирович; Іщенко, Олександр Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Проаналізовано особливості роботи підшипників ковзання прокатного обладнання. Розглянуто методи діагностики підшипників ковзання загального призначення і прокатного обладнання. Запропоновано прямий контроль гранично допустимого зносу підшипників ковзання в експлуатації. Сформульовано основні положення програми проведення консультацій з працівниками технічних служб металургійних підприємств щодо обслуговування, ремонту і експлуатації типових підшипників ковзання та ознайомлення з конструкцією, функціонуванням, наладкою, особливостями експлуатації, обслуговування, ремонту підшипників ковзання з розробленим модулем прямого контролю зносу.

Peculiarities of rolling bearings operation are analyzed. Methods of diagnostics of general purpose sliding bearings and rolling equipment are considered. Direct control of the maximum allowable wear of plain bearings during operation is proposed. It is advisable to provide remote information and consulting services to technical services of metallurgical enterprises for maintenance, repair and operation of crankshaft bearings. Bearings of electric machines of drives of rolls of rolling mills work in extremely difficult conditions with considerable overloads in the environment of the increased vibration. This leads to premature wear of the liner and its fatigue failure. The technical condition of bearings of electric machines of drives of rolls of rolling mills for the purpose of an exception of anemergency stop of production is carried out by indirect control of temperature and vibration. However, these controls do not guarantee an avoidance of an emergency. All problems with working plain bearings can be grouped into three groups: insufficient bearing capacity of the lubricating layer, unregulated clearance between the shaft and the liner, unsatisfactory technical condition of the bearing surfaces. Insufficient bearing capacity of the lubricating layer is more often associated withloss of lubricant properties due to improper maintenance of the lubrication system. The discrepancy between the size of the gap between the shaft and the liner to the normalized value arises from design, technological and operational reasons.
Diagnostics of rolling equipment sliding bearings
Keywords: прокатне обладнання; прямий контроль зносу; дистанційні інформаційно-консультаційні послуги; rolling equipment; direct wear control; remote information and consulting services